Reforming public port authorities through multiple concession agreements: The case of Cyprus - Panayides, Photis; Lambertides, Neophytos; Andreou, Christoforos K. (My University, 2017)
There has been a continuous restructuring of port systems and governance models that deal with the organization and administration of the ports. The main reasons for such restructurings are related to the need for increased commercialization of ports, the inefficient administrative structure, the inability to operate through the application of modern commercial practices and inefficiency in capital investments and in operation. This paper describes and analyzes contextual issues leading to the initiation of port reforms as well as the implementation process and the envisaged outcomes following the changes in governance structure of the Cyprus Port Authority and the main port in Cyprus, the Port of Limassol. The port consists of a container terminal, a general cargo/multi-purpose/ro-ro terminal, and a passenger terminal all operated by the authority. In addition, the CPA was the main provider of marine services such as pilotage, towage etc. The objective has been to commercialize all terminals and marine operations either through one (single concessionaire) or multiple concession agreements. Reference is made to the underlying reasons and need for port reforms. The model adopted prior to the port reform process is described as well as the transfer of responsibilities to the newly created corporate entities. In addition, reference is made to the outcomes of the reform process and in particular the change in governance structure to a more distinct landlord model, the increased financial returns in the short and long term, the changes in pricing and the legal and regulatory reforms and the efficiency changes envisaged.
Keywords: Concession agreements; Port of Limassol; Cyprus; Port governance